ANALYSIS OF FACTORS ASSOCIATED WITH THE INCIDENT OF CENTRAL OBESITY IN ADOLESCENTS IN JAMBI CITY - Solihin Sayuti; Ary Irfan (LLDIKTI Wilayah X, 2023)
Obesity is a condition where a person has a body weight that exceeds the normal limit, causing excessive or abnormal fat accumulation in the body. Obesity can be classified based on measurements of Body Mass Index (BMI) and abdominal circumference. The aim of this study was to determine the factors associated with the incidence of central obesity in adolescents in Jambi City. This quantitative descriptive research uses a cross-sectional study. In this research, the Solvin formula was used to calculate the sample size, which consisted of 96 teenagers living in the working area of the Putri Ayu Community Health Center in 2024.Data collection uses a questionnaire. Data processing takes the form of univariate and bivariate analysis. The analysis used is chi-square. with Confident Interval (CI <95%) with a significance limit (α <0.05). The research was carried out from April to May 2024. The results of the univariate analysis showed that from 96 respondents, 42 people (43.8%) of respondents will be male and 54 people (56.2%) will be female. As many as 59 people (61.5%) of respondents had a poor level of knowledge and 37 people (38.5%) of respondents had a good level of knowledge. A total of 46 people (47.9%) had a light physical activity level, 35 people (36.5%) had a moderate physical activity level and 15 people (15.6%) had a heavy physical activity level. Those with central obesity were 33 people (34.4%) and those with central obesity were 63 people (65.6%). Bivariate analysis showed a significant relationship between gender (p=0.028), knowledge (p= 0.006), physical activity (p= 0.028) andincidence of central obesity in adolescents in Jambi City. Factors that can cause obesity in teenagers include unhealthy eating habits, so it is important to maintain a balanced diet, rich in fiber, and consume fruit and vegetables frequently